Deglaciation records of 17O-excess in East Antarctica: reliable reconstruction of oceanic normalized relative humidity from coastal sites - Winkler R.; Landais A.; Sodemann H.; Dumbgen L.; Prié F.; Masson Delmotte V.; Jouzel J.; STENNI, BARBARA (Climate of the Past, 2012)
We measured 17O and 18O in two Antarctic ice cores at EPICA Dome C (EDC) and TALDICE (TD), respectively, and computed 17O-excess with respect to VSMOW. The comparison of our 17O-excess data with the previous record obtained at Vostok (Landais et al., 2008a) revealed differences up to 35 ppm in 17O-excess mean level and evolution for the three sites. Our data show that the large increase depicted at Vostok (20 ppm) during the last deglaciation is a regional and not a general pattern in the temporal distribution of 17O-excess in East Antarctica. The EDC data display an increase of 12 ppm, whereas the TD data show no significant variation from the Last Glacial Maximum (LGM) to the Early Holocene (EH). A Lagrangian moisture source diagnostic revealed very different source regions for Vostok and EDC compared to TD. These findings combined with the results of a sensitivity analysis, using a Rayleigh-type isotopic model, suggest that normalized relative humidity (RHn) at the oceanic source region (OSR) is a determining factor for the spatial differences of 17O-excess in East Antarctica. However, 17O-excess in remote sites of continental Antarctica (e.g. Vostok) may be highly sensitive to local effects. Hence, we consider 17O-excess in coastal East Antarctic ice cores (TD) to be more reliable as a proxy for RHn at the OSR.